Fungsi Lanskap pada Zona Rehabilitasi di Taman Nasional Gunung Ciremai - Adani, Marini; Sulistijorini, Sulistijorini; Putra, Hirmas Fuady (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Forest rehabilitation on Gunung Ciremai National Park (GCNP) has been carried out since 2008, but it has not yet known the progress of the landscape function of the rehabilitation fields. The progress of landscape function can be evaluated using landscape function analysis method which yields three indexes namely land stability, water infiltration, and land nutrition cycle. This study aims to determine the progress of landscape function in several GCNP rehabilitation zones based on the age of rehabilitation. The research method consist of: (1) determination of research location, (2) microclimate measurement, (3) measurement of soil characteristics, and (4) landscape function analysis (LFA). Land stability in forest and land rehabilitation zones (RHL) were 9, 7, and 5 years old and the natural zones respectively: 57.9%; 54.3%; 48.6%; and 56.1%, respectively. Infiltration in RHL zones aged 9, 7, and 5 years and natural zones respectively: 49%; 39.4%; 31.8%; and 36.2%, respectively. The nutritional cycle in the RHL zone was 9, 7, and 5 years old and the natural zone was 47.9%; 34.6%; 23.4%; and 29.2%. Therefore a rehabilitation zone in GCNP which is seven years or older showed its landscape function has reached even beyond the original landscape function.